Fenomena Penghijrahan Belia Sabah dari Desa ke Bandar-bandar Utama di Malaysia - Haji Abbas, Roslee bin; Binsin, Dzulkiflee Abdullah bin (SOSIOHUMANIKA, 2008)
ABSTRACT: There has been for some time substantial concern regarding the loss of young people in rural communities. There is a sense that most rural communities offer few opportunities for their young people, requiring them to leave their urban communities, most likely not to return. While there is a considerable body of research on migration per se, relatively little is currently known about rural-to-urban youth migration areas in Sabah. Rural youth migration is nothing new in Malaysia. At any given time, young people will have an expectation to leave home to explore, pursue higher education, search for new job opportunities, and so on. The situation has fueled high rural-to-urban migration of youth in that age group, the phenomenon leads to further rural decline and urban destitution. The primary objective of this study is to determine the reason for rural-to-urban migration of youth and young adults of leaving the home community and/or state. This study also examines toward understanding the impact of these experiences on the rural-to-urban youth migration patterns of this age group. Our study is the result of one year conducting field research on rural-to-urban youth migration, with 30 of those days spent in the factories in the Klang valley, Shah Alam, Kota Kinabalu Industrial Park (KKIP), and shopping malls to focus our investigation on the youth community employed in these factories. Key words: young people, rural community, urban community, and process of modernization and urbanization.Â Â Â About the Authors: Roslee bin Haji Abbas ialah Pensyarah pada Program Sosiologi & Antropologi Sosial, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau melanjutkan pengajian ke Southern NewÂ  Hampshire University, USA, pada Ogos 1987 dan memperolehi ijazah Sarjana Muda Sains Kemasyarakatan (Psikologi & Sosiologi) dan ijazah Sarjana pada 1990 dalam bidang Pembangunan Ekonomi Komuniti Antarabangsa di universiti yang sama. Bidang kepakaran beliau ialah pembangunan komuniti, belia, remaja dan masyarakat, devian sosial dan pembangunan sosial. Beliau boleh dihubungi untuk sebarang urusan akademi, dengan alamat e-mail: rosleeabbas@yahoo.com Dzulkiflee Abdullah bin Binsin ialah Pensyarah pada Program Komunikasi, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Beliau melanjutkan pengajian ke Indiana State University, USA, pada tahun 1985; dan memperolehi ijazah Sarjana pada tahun 1987 daripada universiti yang sama dalam bidang Pengurusan Penyiaran dan Penerbitan. Bidang kepakaran beliau ialah pengurusan penyiaran radio, sama ada untuk di bandar mahupun luar bandar. Beliau boleh dihubungi untuk sebarang urusan akademi, dengan alamat e-mail: dzulkifa@ums.edu.myHow to cite this article? Haji Abbas, Roslee bin & Dzulkiflee Abdullah bin Binsin. (2008). âFenomena Penghijrahan Belia Sabah dari Desa ke Bandar-bandar Utama di Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.2 [November], pp.331-352. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112.Chronicle of the article: Accepted (June 14, 2008); Revised (August 15, 2008); and Published (November 20, 2008).